Glycerol Waste to Bio-Ethanol: Optimization of Fermentation Parameters by the Taguchi Method - Chilakamarry, Chaitanya reddy; Mimi Sakinah, A. M.; Zularisam, A. W.; Khilji, Irshad Ahamad; Kumarasamy, Sudhakar (Hindawi Publishing Corporation, 2022)
Global attention caused by pollutants and greenhouse gas emissions leads to alternative fuels that decrease the dependence on fossil fuels and reduce the carbon footprint that preceded the development of biodiesel production. Glycerol residue is generated more significantly from the biodiesel industry as a byproduct and is left as waste. In this study, we utilized glycerol residue from the biodiesel industry as an excellent opportunity to convert ethanol by bioconversion. The waste glycerol was used as a good and cheap carbon source as a substrate to synthesize ethanol by immobilizing E. coli cells. The screening of parameters such as mass substrate, temperature, inoculum size, and fermentation time was carried out using the one-factor-at-a-time (OFAT) technique. The Taguchi model employed optimization of fermentation parameters. The process parameters showed the mass substrate glycerol of 20 g with an inoculum size of 20%, and 12 hours yielded the ethanol concentration of 10.0 g/L.